A data‐driven examination of apathy and depressive symptoms in dementia with independent replication. Issue 1 (5th February 2023) - Vasconcelos Da Silva, Miguel; Melendez‐Torres, Gerardo Javier; Ismail, Zahinoor; Testad, Ingelin; Ballard, Clive; Creese, Byron; ,
Abstract: Apathy is one of the most common neuropsychiatric symptoms (NPS) and is associated with poor clinical outcomes. Research that helps define the apathy phenotype is urgently needed, particularly for clinical and biomarker studies. We used latent class analysis (LCA) with two independent cohorts to understand how apathy and depression symptoms co‐occur statistically. We further explored the relationship between latent class membership, demographics, and the presence of other NPS. The LCA identified a four‐class solution (no symptoms, apathy, depression, and combined apathy/depression), reproducible over both cohorts, providing robust support for an apathy syndrome distinct from depression and confirming that an apathy/depression syndrome exists, supported by the model fit test with the four‐class solution scores evidencing better fitting (Bayesian information criterion adjusted and entropy R 2 ). Using a data‐driven method, we show distinct and statistically meaningful co‐occurrence of apathy and depressive symptoms. There was evidence that these classes have different clinical associations, which may help inform diagnostic categories for research studies and clinical practice. Highlights: We found four classes: no symptoms, apathy, depression and apathy/depression. Apathy conferred a higher probability for agitation. Apathy diagnostic criteria should include accompanying neuropsychiatric symptoms.